PERWUJUDAN NILAI AL-BIRR WA AL-TAQWA DALAM KEPEMILIKAN - Anisa Ilmia (UIN Sunan Gunung Djati Bandung, 2020)
ABSTRACTIslamic economics is an economic system that is different from the capitalist economic system and the socialist economic system, one of which is the ownership rights. Islam recognizes the existence of human ownership, but still emphasizes that Allah SWT is the absolute owner of everything include the universe so that what humans have is only a mandate that must be obtained and utilized in accordance with Allah’s rules. Ownership is the integration of the Islamic economic system so that it contains an element of morality that will give birth to the value of the khilafah and the value of al-birr wa al-taqwa (goodness and obedience) in which both values are centered on divine value (Ilahiyah). The realization of these values in ownership has implications for the well-being and economic equalization to achieve “falah” (bliss of the world and the hereafter). Keywords : ownership, morality, value, Islamic economic, obedience